Como chegamos até aqui: a migração da memória e os instrumentos de controle - Silva, Silvio Ferreira da (2016)
This paper provides an overview of the relationship between man and machine, specifically the computer. It is a reflexive work, addressing the expanded world of culture in an exploratory approach on memory and the evolution of its artificial supports. It begins narrating the historical evolution to the present time, focusing in the inventor geniuses, and its works., whose improvements resulted in achievements in technology. The text is subsidized by considerations regarding collection and data quality, design and content management algorithms and artificial intelligence. This study highlights the ubiquity of this intelligence in everyday society, as well as the submission of the society to its designs. It analyzes the impact that technology has on citizens from the perspective of contemporary thinkers, especially Vilém Flusser and Kurt Kurzweil, and their visions of the future. It also approaches speech surveillance, ethics, error and fraud. This paper exposes the risks to which the society is subject to undergoing processes whose managers are unaware of, with practical examples of damage that occurred in the recent past. At last, the discussion proposes the challenge of creating a code of ethics for the developers of software, because the dilemmas, social and legal, that emerge every now and then, for which there is not yet clarity of approach